Cosmopolitan travellers in a "deterritorialized" world: transcultural encounters in Pico Iyer's The Global Soul: Jet Lag, Shopping Malls, and the Search for Home (2000). Issue 3 (1st September 2020) - Butt, Nadia
ABSTRACT: This paper explores cosmopolitan travellers with reference to transcultural encounters in Pico Iyer's travelogue The Global Soul: Jet Lag, Shopping Malls, and the Search for Home . My main argument is that the travelogue, covering Iyer's lifetime in America, Europe, and Asia, not only illustrates the different aspects of the 'global soul' as a 'global traveller' but is a compelling statement on hybrid identities and multiple cultural connections in the speed age of modernity in which travel and mobility urge a reassessment of fixed national, geographical, cultural, and linguistic boundaries. Using different images of our modern world as metaphors of globalisation such as moving houses, worldwide travel or the airport, Iyer gives us a new understanding of belonging in our present era. Therefore, the paper concludes that the Global Soul in Iyer's travelogue points to cosmopolitan travellers in our deterritorialized age for whom identity is as fluid as the notion of home.